2016
DOI: 10.9775/kvfd.2016.15904
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoksin B1’in Fare Beynine Geçişi Üzerine BCRP ve P-gp Modülatörlerinin Etkisi

Abstract: This study was conducted to determine whether the plasma and brain concentrations of AFB1 are affected by the modulation of P-gp and BCRP using zosuquidar (ZQR) and prazosin (PRZ), respectively. In this study, a total of 40 healthy adult male BALB/c mice (32±3.7 g) were used. The animals were randomly divided into 5 groups, with 8 animals per group. Group 1 was used for method validation. Group 2 (AF) received intraperitoneal AFB1 at a dose of 20 mg/kg of body weight. Groups 3 (AF+PRZ), 4 (AF+ZQR), and 5 (AF+P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Tras (Tras et al, 2017) conducted the first in vivo experimental study intended to verify if plasma and brain concentrations of AFB1 are affected by the modulation of trans-membrane proteins, namely the ATP-binding cassette transporter superfamily (e.g. Tras (Tras et al, 2017) conducted the first in vivo experimental study intended to verify if plasma and brain concentrations of AFB1 are affected by the modulation of trans-membrane proteins, namely the ATP-binding cassette transporter superfamily (e.g.…”
Section: Rats and Micementioning
confidence: 99%
“…Tras (Tras et al, 2017) conducted the first in vivo experimental study intended to verify if plasma and brain concentrations of AFB1 are affected by the modulation of trans-membrane proteins, namely the ATP-binding cassette transporter superfamily (e.g. Tras (Tras et al, 2017) conducted the first in vivo experimental study intended to verify if plasma and brain concentrations of AFB1 are affected by the modulation of trans-membrane proteins, namely the ATP-binding cassette transporter superfamily (e.g.…”
Section: Rats and Micementioning
confidence: 99%
“…The function of P-gp can be modulated to protect tissues and to alter the effect of drugs. Various drugs and foods lead to drug-drug and drug-food interactions by causing induction and inhibition of these carrier proteins (Dresser et al, 2003;Greiner et al, 1999;Hebert et al, 1999;Kirn et al, 1999;Matheny et al, 2001;Tras et al, 2017;Westphal et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxin B1 (AFB1), which is a well-known hepatic carcinogen, is one of the most toxic mycotoxins. AFB1, a common food contaminant, causes immunodeficiency, reproductive problems, growth impairment, acute toxication, economic losses, and damage to organs such as the heart, kidney, brain (Tras et al 2017, Shan 2020 It was reported that AFB1 passes into the brain and has a toxic effect on the central nervous system with its effect on both nerve cells and the blood-brain barrier (Qureshi et al 2015, Mehrzad et al 2017, Tras et al 2017). In addition, AFB1 has destructive effects on subcellular organelles such as mitochondria and molecules such as DNA (Ge et al 2017, Shan 2020.…”
Section: Introductionmentioning
confidence: 99%